Changes in household fuel expenditure associated with improvements in building energy efficiency - John Curtis; Anne Pentecost (The Economic and Social Research Institute (ESRI), 2014)
This paper combines data on residential building energy performance certificates (EPC) and household energy expenditure to estimate expenditure equations (Engel curves) as a function of building energy efficiency and household characteristics. Engle curves for gas, oil, electricity, solid fuel, and aggregate fuel expenditure are estimated for a sample of 5,891 households in the Republic of Ireland. With building energy performance measured using a 7 point letter scale (A to G) our results find that households living in relatively energy inefficient properties spend between exteuro160- exteuro419 per annum more on energy than households in B rated properties. In percentage terms a one letter improvement in building energy rating is associated with a 4-10% change in total household energy expenditure. When energy use for entertainment, cooking, and laundry purposes are excluded, this represents approximately a 6-14% change in energy expenditure for heating, lighting and ventilation purposes (i.e. building related energy).
Keywords: 330